PENERIMAAN DAN PREFERENSI RUMAH TANGGA DAN JASA BOGA TERHADAP MINYAK GORENG CURAH YANG DIFORTIFIKASI KAROTEN DARI RED PALM OIL (RPO) - Sri Anna Marliyati; Tika Nurmalasari; Lilik Kustiyah; Drajat Martianto (Food and Nutrition Society of Indonesia, 2012)
The purpose of this research was to find out acceptance and preference of households and catering to non-branded cooking oil fortified with carotene from Red Palm Oil (RPO). The subjects in this study was 30 people respectively for each households and catering. Data was collected through interviews and discussions using questionnaires. Data of subjects acceptance and preference were analyzed using descriptive statistics and Friedman test. Average cooking oil used by household subjects was 0.185+0.070 kg/day and catering was 3.87+2.46 kg/day. Most households (73.3%) and catering (66.7%) could not accept cooking oil fortified with carotene from RPO due to its colour and aroma. Fortified cooking oil had orange colour and rotten aroma (of odor). More than half of households (66.7%) and catering (63.3%) could not accept the fried product using fortified cooking oil because of its yellow colour. Friedman test showed that there were differences in both subjects acceptance to nonfortified and fortified non-branded cooking oil (p<0.05). Both household and catering subjects preferred nonfortified cooking oil.